Rekonstruksi Konsep Dasar Kurikulum dalam Menjawab Tantangan Pendidikan di Era Digital - Alikha Naya Dwi Azkhia; Andini, Flora (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid progress of digital technology has profoundly changed various aspects of society, including the field of education. This evolution demands a reevaluation of the fundamental concepts of the curriculum to ensure it remains modern and applicable. This paper aims to explore and assess the process of redesigning essential curriculum principles to address the challenges faced in education within the digital age. It utilizes a literature review of different resources related to curriculum development and the transformation of education in the digital context. The findings indicate that the curriculum in today's digital landscape focuses not only on knowledge acquisition but also on fostering essential 21st-century skills, such as critical thinking, innovation, teamwork, and digital literacy. The curriculum needs to be flexible and adaptable, integrating technology into teaching and learning practices. In this reimagining process, educators must act as facilitators and be well-versed in technology. Thus, refreshing the core ideas of the curriculum is a vital initiative to establish an education system that is adaptable, innovative, and capable of developing skilled individuals in the digital age.